EFEKTIFITAS KECERDASAN EMOSIONAL DENGAN KETERAMPILAN MENGGIRING BOLA DALAM PERMAINAN SEPAKBOLA - Bismar, Ahmad Rum; Sudiadharma, Sudiadharma (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study aims to see the effectiveness of emotional intelligence with dribbling skills in soccer games among students of the Faculty of Sport Sciences, Makassar State University. The study population consisted of all students of the Faculty of Sport Science, State University of Makassar who had passed the TP subject. Football with a total sample of 30 people of the 2017 batch of Sports Coaching Education Department. This type of research is correlation, data collection is done by testing techniques and data processing is done by statistical analysis of the correlation with a value of 0.420 Sig. (2-tailed) 0.021. Based on the table of correlation assessment criteria, it is concluded that emotional intelligence has an effectiveness on dribbling skills in students of the Faculty of Sport Sciences, Makassar State University